2014
DOI: 10.3174/ajnr.a3912
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Anisotropy and Diffusivity along the Medulla Oblongata and the Whole Spinal Cord in Adolescent Idiopathic Scoliosis: A Pilot Study Using Diffusion Tensor Imaging

Abstract: BACKGROUND AND PURPOSE:Disturbed somatosensory evoked potentials have been demonstrated in patients with adolescent idiopathic scoliosis (but this functional delay was found to originate above the C5-6 level, while the lower cord level was unaffected). Together with MR imaging observation of tonsillar ectopia and a relatively tethered cord, we hypothesized that there is disturbed mean diffusivity integrity along the spinal cord. In this study, advanced DTI was used to evaluate whether there was underlying decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 36 publications
1
21
1
1
Order By: Relevance
“…Higher postural stability is preferable for patients who have difficulty maintaining their balance e.g. adults with disability and some pre-operative AIS [28,29]. Considerations are needed for a patient's positioning in each position.…”
Section: Discussionmentioning
confidence: 97%
“…Higher postural stability is preferable for patients who have difficulty maintaining their balance e.g. adults with disability and some pre-operative AIS [28,29]. Considerations are needed for a patient's positioning in each position.…”
Section: Discussionmentioning
confidence: 97%
“…In AIS, some authors have concentrated on muscle and peripheral nerve disturbances, but in other studies impairment of the spinal cord and different pattern of brain activation has been published [7][8][9]. These observations demonstrate that central nervous system involvement with abnormal sensorimotor integration may underlie the pathogenesis of idiopathic scoliosis [5,10].…”
Section: Introductionmentioning
confidence: 97%
“…20 Our finding might shed light on the pathoanatomical origin of abnormal SEP in AIS patients, particularly in patients with Cobb angle over 40 degrees. 18 …”
Section: Discussionmentioning
confidence: 60%
“…This provides further neurophysiological support to our previous finding on imaging. 20 Reports on the pre-operative SEP assessment on AIS patients with different severity were scarce. The results from 1 of the 2 reported studies with pre-operative electrophysiological and radiological evaluation in 100 adolescent patients admitted for surgery showed that SEP latency increased in 56% of the patients, and 3% of whom was found to have intraspinal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation